Pendidikan Multikultural Kebudayaan Ortomotif Dalam Pluralisme Beragama - Tamrin Fathoni; Lisma Meilia Wijayanti (CV Edujavare Publishing, 2023)
Indonesia is a country rich in cultural and religious diversity. The purpose of writing this work is to describe the concept of cultural multicultural education, cultural multicultural education as a means to strengthen religious pluralism in Indonesia and the implementation of ortomotive cultural education in religious pluralism in Indonesia. Writing this work using the method of literature review. The approach used by the author through descriptive. To obtain data through documentation and current issues regarding multicultural education or automotive culture in religious pluralism. The results of this work are a). Cultural multicultural education as an educational approach that recognizes and values cultural diversity, increases tolerance for differences, broadens understanding of culture, and promotes harmonious social relations among students with different cultural backgrounds. b). Multicultural education strengthens religious pluralism in Indonesia by recognizing and respecting the diversity of ethnicities, religions, cultures and political views in society. and c). Ortomotive cultural education can be applied in multicultural education in Indonesia by integrating different cultural content and religious values, and paying attention to cognitive levels and critical, humanist, and free approaches in learning.